Nutritional and Albumin Content of Swamp Fishes from Merauke, Papua, Indonesia - Susilowati, Rini; Sugiyono, Sugiyono; Chasanah, Ekowati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Study on chemical content of swamp fishes from Merauke has been conducted to obtain nutritional status  of these fishes. Sampling was conducted  twice (August and November 2015) in Merauke. There were six dominant fish species, namely striped snakehead (Channa striata), nile tilapia (Oreochromis niloticus), tade gray mullet (Liza tade), philippine catfish (Clarias batrachus), barramundi (Lates calcarifer), and climbing perch (Anabas testudineus). Result on proximate analysis showed that the fishes had moisture content of 75.73±0.25%-81.45±0.04%, ash 0.94±0.01%-1.26±0.21%, protein 17.11±0.09%-18.92±0.05%, and lipid 0.59±0.19%-3.80±0.63%. The dominant essential amino acid of 6 swamp fishes from Merauke was lysine followed by leucine. Meanwhile the dominant non-essential amino acid was glutamic acid (32.26+0.61 mg/g), followed by aspartic acid. Calcium (Ca) was the dominant macro mineral for all fishes studied, being the highest was in nile tilapia (328.76±8.14 mg/100 g). Micro mineral was dominated by the presence of Selenium (Se) which the highest was in nile tilapia (0.084±0.005 mg/100g). These fishes were also rich in albumin, being the highest was stripe snakehead (138.59±1.68 mg/g). The average of total fatty acid showed that the fishes had saturated fatty acid (SFA) content of 46.30±0.27%, monosaturated fatty acid (MUFA) 9.20±1.6%  and polyunsaturate fatty acid (PUFA) 34.49±0.44% of total fatty acid. From the result, it can be concluded that fish harvested from swamp of Merauke and surrounding area had a good nutritional value.